Benchmarking of Industrial Synthetic Graphite Grades, Carbon Felt, and Carbon Cloth as Cost-Efficient Bioanode Materials for Domestic Wastewater Fed Microbial Electrolysis Cells - Roubaud, Emma; Lacroix, Rémy; Da Silva, Serge; Etcheverry, Luc; Bergel, Alain; Basséguy, Régine; Erable, Benjamin (Frontiers in Energy Research, 2019)
Anode material selection is crucial when it comes to building up-scaled microbial electrolysis cells (MEC), has it as a huge influence on the achievable current density and account for a large part of the MEC total investment cost. Graphite is a material that is perfectly suited to the creation of up-scaled bioanodes as it is conductive, chemically stable, biocompatible, and relatively cheap but there are a very large number of commercially available grades of industrial graphite. In this study, five grades of industrial synthetic graphite (named G1–G5) were bench tested to select the most suitable grade for future development of 3D bioanode for domestic wastewater (dWW) fed MEC application. The five grades of graphite have been selected with similar physico-chemical and surface properties (electrical resistivity, surface roughness, and hydrophobicity) theoretically appropriate for EA biofilm development. Nevertheless, significant current density disparities where observed with the five graphite grades, which can certainly be explained by the fabrication procedures of the respective material grades. With the graphite grade giving the most efficient anodes (G3), an average steady state current density of 2.3 A/m2 was produced, outperforming the other grades by at least 15%. Even though all graphites had very close physico-chemical characteristics, the grade had a clear significant influence on the current densities produced. G3 graphite was finally compared to carbon felt (CF) and carbon cloth (CC) both in terms of bio-electrochemical current production and bacterial communities colonizing electrodes. G3 bioanodes outperformed CF and CC bioanodes by 50% in term of steady state current density. Biofilms microbial population analysis showed that the Geobacter species was present at 82% on G3 bioanodes, 39% on CF bioanodes, and 61% on CC bioanodes when it was only present at 0.06% in the activated sludge used as inoculum. This significant difference in bacterial enrichment could come from the huge gap between materials resistivity, as graphite resistivity is 200-fold lower than CF and CC resistivities. The strongly hydrophilic surface of G3 graphite was also certainly beneficial for biofilm development compared to the hydrophobic surfaces of CF and CC.